The Role of Binders and Fillers in the Study of Concrete Properties - Umarov Shodiljon Abdug‘ofurovich; Abobakirova Zebuniso Asrorovna (International Journal on Orange Technologies, 2023)
This article is an analysis of the directions of use with an assessment of the possibility of using glass grinding clay in the production of concrete. The use of modern technological approaches in the formation of products to significantly improve the quality of concrete and increase its properties.It consists of the preservation of Natural Resources, the use of waste materials and the production of concrete with improved properties by adding glass waste to concrete.